The effects of genotypic and yearly variations on the egg volumes of the Mute Swan Cygnus olor - Bacon, P J; Mountford, M D (Wildfowl, 1990)
Measurements of Mute Swan eggs are highly replicable between different observers. Analysis of the egg volumes of 119 clutches of Mute Swans measured in four years gave a mean volume of 332 cm^3 (SD = 27) and partitioned the variance into three random components (within clutch; between bird; bird/year-interaction) and two 'fixed' effects (four year-to-year differences and three female genotypes at a biochemical marker locus). The same females consistently laid similar sized eggs in different years, but it was concluded that there were small but real differences between eggs laid by the different genotypes. It is unnecessary to measure every egg in a clutch to estimate adequately the average egg volume of that clutch. Other studies show that larger eggs would, in Mute Swans more than most species, be expected to confer better cygnet survival, but there is presently no direct evidence that this is so.